Scandal, Social Movement, and Change: Evidence from #MeToo in Hollywood - Luo, Hong; Zhang, Laurina (Management Science, 2022)
Social movements have the potential to effect change in strategic decision making. In this paper, we examine whether the #MeToo movement, spurred by the Harvey Weinstein scandal, leads to changes in the likelihood of Hollywood producers working with female writers on new movie projects. Because #MeToo affected the entire industry, we use variation in whether producers had past collaborations with Weinstein to investigate whether and how #MeToo may spur change. We find that producers previously associated with Weinstein are, on average, about 35% more likely to work with female writers after the scandal than they were before, relative to nonassociated producers, and the size of this effect increases with the intensity of the association. Female producers are the main drivers of our results, perhaps because they are more likely than male producers to resonate with the movement’s cause and face relatively low costs of enacting change. Changes made by other groups, such as production teams with the most intense association with Weinstein and less experienced all-male teams, may be better explained by motivations to mitigate risk. We also find that producers do not sacrifice writer experience by hiring more female writers and that both experienced and novice female writers have benefited from the increased demand. Our study shows that social movements that seek to address gender inequality can, indeed, lead to meaningful change. It also provides perspective for thinking about whether, and to what extent, changes may occur in broader settings. This paper was accepted by Isabel Fernandez-Mateo, organizations.